а) a⁴-b⁴=(a²+b²)(a²-b²)=(a²+b²)(a-b)(a+b)
б) x⁴-x²=x²(x²-1)=x²(x+1)(x-1)
в) am³-an³=a(m³-n³)=a(m-n)(m²+nm+n²)
г) a⁴-16=a⁴-4²=(a²+4)(a²-4)=(a²+4)(a-2)(a+2)
д) 1-c⁴=(1+c²)(1-c²)=(1+c²)(1+c)(1-c)
е) x²-16x⁴=x²(1-4²x²)=x²(1+4x)(1-4x)
а) a⁴ - b⁴ = (a²)² - (b²)² = (a² - b²) (a² + b²) = (a - b) (a + b) (a² + b²)
б) x⁴ - x² = x²(x² - 1) = x²(x - 1)(x + 1)
в) am³-an³ = a(m³ - n³) = a(m-n)(m² + mn + n²)
г) a⁴ - 16 = (a²)² - 4² = (a² - 4)(a² + 4) = (a - 2)(a + 2)(a² + 4)
д) 1 - c⁴ = 1² - (c²)² = (1 - c²)(1 + c²) = (1 - c)(1 + c)(1 + c²)
е) x²-16x⁴ = x²(1 - 16x²) = x²(1 - (4x)²) = x²(1 - 4x)(1 + 4x)
а) a⁴-b⁴=(a²+b²)(a²-b²)=(a²+b²)(a-b)(a+b)
б) x⁴-x²=x²(x²-1)=x²(x+1)(x-1)
в) am³-an³=a(m³-n³)=a(m-n)(m²+nm+n²)
г) a⁴-16=a⁴-4²=(a²+4)(a²-4)=(a²+4)(a-2)(a+2)
д) 1-c⁴=(1+c²)(1-c²)=(1+c²)(1+c)(1-c)
е) x²-16x⁴=x²(1-4²x²)=x²(1+4x)(1-4x)
а) a⁴ - b⁴ = (a²)² - (b²)² = (a² - b²) (a² + b²) = (a - b) (a + b) (a² + b²)
б) x⁴ - x² = x²(x² - 1) = x²(x - 1)(x + 1)
в) am³-an³ = a(m³ - n³) = a(m-n)(m² + mn + n²)
г) a⁴ - 16 = (a²)² - 4² = (a² - 4)(a² + 4) = (a - 2)(a + 2)(a² + 4)
д) 1 - c⁴ = 1² - (c²)² = (1 - c²)(1 + c²) = (1 - c)(1 + c)(1 + c²)
е) x²-16x⁴ = x²(1 - 16x²) = x²(1 - (4x)²) = x²(1 - 4x)(1 + 4x)